2010
DOI: 10.2224/sbp.2010.38.9.1243
|View full text |Cite
|
Sign up to set email alerts
|

Social Attitudes of Turkish Students Towards Participation in Physical Education and Sport

Abstract: The aim of the study was to determine the factors that are effective in encouraging Turkish high school students to try sports and to identify ways to increase the number of students taking part in sport. The importance of sport in acquiring appropriate social attitudes, making good use of free time, and acquiring self-discipline and positive attitudes by learning patience, anger management, tolerance, courage, affection, and competition has been noted. In the study it was found that factors that are effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Little has been written about leisure in Islamic cultures (Aslan, 2009;Martin & Mason, 2011;Roberts, 2011) although more examples in English language journals have appeared in the latter part of the first decade of the twenty-first century (e.g., ArabMoghaddam et al, 2007;Aydin, 2009;Goral, 2010;Koca et al, 2009). Roberts (2011) suggested that as countries modernize, whether Christian or Islamic, greater separation begins to occur between religion and government, which allows for more individual freedom often expressed in forms of leisure.…”
Section: Background Literaturementioning
confidence: 99%
“…Little has been written about leisure in Islamic cultures (Aslan, 2009;Martin & Mason, 2011;Roberts, 2011) although more examples in English language journals have appeared in the latter part of the first decade of the twenty-first century (e.g., ArabMoghaddam et al, 2007;Aydin, 2009;Goral, 2010;Koca et al, 2009). Roberts (2011) suggested that as countries modernize, whether Christian or Islamic, greater separation begins to occur between religion and government, which allows for more individual freedom often expressed in forms of leisure.…”
Section: Background Literaturementioning
confidence: 99%
“…There is also an abundance of evidence suggesting that a range of social health benefits can be gained from sport involvement, particularly for youth. For example, the development of social ties comprise an essential source of enjoyment and intrinsic motivation for children, both of which are key predictors of continuation behaviour (Fraser- Thomas, Côté, & Deakin, 2008;Goral, 2010;Kirk & MacPhail, 2003;Ullrich-French & Smith, 2006). Moreover, social health benefits can be observed in the way that sport participation encourages interactions between interracial peers and improves attitudes toward cultural and political issues (Hartmann, Sullivan, & Nelson, 2011;Nathan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%